-(c-5)=2c=

Simple and best practice solution for -(c-5)=2c= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(c-5)=2c= equation:



-(c-5)=2c=
We move all terms to the left:
-(c-5)-(2c)=0
We add all the numbers together, and all the variables
-2c-(c-5)=0
We get rid of parentheses
-2c-c+5=0
We add all the numbers together, and all the variables
-3c+5=0
We move all terms containing c to the left, all other terms to the right
-3c=-5
c=-5/-3
c=1+2/3

See similar equations:

| 3-x/11=-11 | | m=91 | | x+7+2x=4x-12 | | x*9-81=x*4-6 | | 4x+3-5=14 | | 14=10-2/3x | | j/3+13=16 | | 4/y+3=5/17 | | 15=n/4+11 | | X+.2x=240 | | 1/4x-(x+1/5)=1/20(x+4) | | -4.9x^2+5x-1000=0 | | 2z+4=34 | | 14=8+2k | | x+8+9=2x+8 | | -1+3x=-3x+25 | | 35-x=3(x=5) | | -6x-7=5x-17 | | (5x+2)+(3x+5)+(5x+10)+(4x+15)+(8x+8)=540 | | 1/3x-(x+1/2)=1/6(X+2) | | 4(5y−1)=3(6y+7) | | 8p+5=77 | | -5.2=-1.3y | | X=5+0.75x | | 4+14=-46-6x | | 2(3x+4)=-2(6+x) | | 5+2x-3=5x-5 | | 33.8c=32+1.8c | | 2r+r+r=12 | | 7x=21=105 | | u=3u-50 | | u=30u-50 |

Equations solver categories